Transcriptional Comparison Investigating the Influence of the Addition of Unsaturated Fatty Acids on Aroma Compounds During Alcoholic Fermentation - Yan, Guo-Liang; Duan, Liang-Liang; Liu, Pei-Tong; Duan, Chang-Qing (Frontiers in Microbiology, 2019)
The levels of unsaturated fatty acids (UFAs) in grape must significantly influence yeast metabolism and the production of aroma compounds. In this work, cDNA microarray technology was applied to analyze the transcriptional discrepancies of wine yeast (commercial wine yeast Lalvin EC1118) fermenting in synthetic grape must supplemented with different concentrations of a mixture of UFAs (including linoleic acid, oleic acid and α-linolenic acid). The results showed that the initial addition of a high level of UFAs can significantly enrich the intracellular UFAs compared to the low addition of UFAs and further increase the cell population and most volatiles, including higher alcohols and esters, except for several fatty acids. Microarray analyses identified that sixty-three genes were upregulated, and ninety-one genes were downregulated during the different fermentation stages. The up-regulated genes were involved in yeast growth and proliferation, stress responses and amino acid transportation, while the repressed genes were associated with lipid and sterol biosynthesis, amino acid metabolism, TCA cycle regulation, mitochondrial respiration and stress responses. Unexpectedly, the genes directly related to the biosynthesis of volatile compounds did not vary substantially between the fermentations with the high and low UFA additions. The beneficial aromatic function of the UFAs was ascribed to the increased biomass and amino acid transportation, considering that the incorporation of the additional UFAs in yeast cells maintains high membrane fluidity and increases the ability of the cells to resist deleterious conditions. Our results highlighted the importance of UFAs in the regulation of aroma biosynthesis during wine fermentation and suggested that the improvement of the resistance of yeast to extreme stresses during alcoholic fermentation is essential to effectively modulate and improve the production of aroma compounds. A potential way to achieve this goal could be the rational increase of the UFA contents in grape must.